The effect of human resource competency and control management on budget efficiency - Ishthifa’iyah Ishthifa’iyah; Wahyu Helmy Damayanti Sukisworo (Institute of Accounting Research and Novation (IARN), 2026)
For an organization, achieving sustainability and competitive advantage depends heavily on budget efficiency as a key factor. This study examines the influence of human resource competency (HRC) and control management (CM) on budget efficiency at PT Swabina. A quantitative approach was used with a survey method, involving 35 employees directly involved in budgeting through saturated sampling techniques. The data were analyzed using the PLS-SEM method with the help of SmartPLS. The results show that HR Competence has a positive and significant effect on Budget Efficiency, with a path coefficient of 0.443 (P<0.05). Similarly, Control Management has a significant positive effect with a coefficient of 0.431 (P<0.05). Simultaneously, both variables explain 67.2% of the variation in Budget Efficiency (R² = 0.672). These findings emphasize the importance of improving employee competency and strengthening control systems to support corporate budget efficiency. Thus, the combination of competent human resources and a strong control system is a major factor in achieving budget efficiency. These findings underscore the importance of companies investing simultaneously in developing human resource capabilities and strengthening internal control mechanisms to improve financial performance.